Preliminary outcomes of a hybrid-digital parenting intervention in routine services in Malaysia - Senesathith, Vanisa; Lachman, Jamie; Rajandiran, Durgesh; Han, Qing; Bala, Amy; Melendez-Torres, G. J.; Gardner, Frances; Vyas, Seema; Cooper, Hal; Facciolà, Chiara; Mohd Jalil, Laila Nasuha; Mohd Nadzri, Farah Zeehan; et al. (SAGE Publications, 2026)
Purpose: This paper examined pre-post changes in child maltreatment and associated outcomes among caregivers of children ages 2–6 years who participated in a hybrid-digital parenting intervention delivered by civil society organizations (CSOs) in Malaysia. Methods: Data were collected by five CSOs between January and April 2024 in Kuala Lumpur and Selangor. The intervention included a parenting support chatbot, WhatsApp groups, and two in-person sessions. Results: Of 133 caregivers, only 36 completed both baseline and post-intervention assessments, resulting in a 73% attrition rate. No significant changes were found in child maltreatment (p = .698), though improvements in positive parenting (β= 1.75 [0.19, 3.32]) and reductions in child externalizing behaviors (IRR = 0.70 [0.53, 0.93]) were observed. Discussion: This is the first study to explore a hybrid-digital parenting intervention in routine services in Malaysia. It shows promise for improving parenting outcomes but also highlights challenges in data collection that should be addressed.